The Influence Of Wet And Dry Seasons Conditions On Chemical Compositions, Properties And Total Suspended Solids Of Different Water Source And Type In Riau-Oil Fields - Tjuwati Makmur; Nuraini Nuraini (Testing Center for Oil and Gas LEMIGAS, 2009)
Change of wet and dry seasons conditions have major impact, the results of chemical compositions concentration determination for RRV, RST, ORK, KWT, KWL and PRD water samples (sampling in dry seasons) are higher than in wet seasons. All of the analyzed water samples don’t results in the occurrence of calcium sulfate. Only PRD water has potential to form calcium carbonate scale, because pH value in a range of 7.85 – 8.10 (pH >7). The RRV, RST, ORK, KWT, KWL and PRD (sampling in wet and dry seasons) have poor injection water quality, because the concentrations of total suspended solids (TSS) in the analyzed water samples are higher than 8 ppm.